Microstructure and integrity of multilayer ceramic coating with alumina top coat on silicon carbide by laser chemical vapor deposition. Issue 7 (1st April 2023) - Usukawa, Ryutaro; Katsui, Hirokazu; Shimoda, Kazuya; Kondo, Sosuke; Hotta, Mikinori
Abstract: Thin double-layer coatings comprising an alumina top coat and mullite bond coat were deposited on SiC substrates by laser chemical vapor deposition (CVD). The effect of the presence of mullite bond coat and the phases of alumina top coat on the structural integrity against the thermal residual stress loaded by the high-temperature CVD process was examined by microstructural characterization and simulative consideration. A laminated layered structure having a dense γ-alumina top surface with a cone-like morphology are grown at a deposition temperature of 1323 K, whereas an α-alumina top layer comprising densely packed faceted grains was grown at 1473 K. The interfaces between the SiC and mullite layers were coherent owing to the formation of a thin transition layer. The γ-alumina layer formed an adhesive interface bordering the mullite layer, whereas small residual defects were formed in the α-alumina layer bordering the mullite layer. Spacings of surface cracking induced by the high-temperature deposition process in the double-layer coatings were approximately half of those in the coatings without mullite layers. As simulative results by finite element method suggested, the double-layer coatings were experimentally verified to be more tolerant to the formation of surface cracks and interfacial delamination, compared to single-layer coatings without the mullite bond layers.